Save or pay-as-you-go: The effcts of ageing on optimal retirement funding - Christian Hott (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Ageing of most societies is driven by two factors: (1) birth rates are declining and (2) people are living longer. These developments have substantial effects on economies and, in particular, on the funding of our living standards in retirement. We develop an overlapping generation model in order to analyse the effects of ageing on the efficiency of retirement savings relative to pay-as-you go systems. Our results indicate that more wealth should be transferred from the young to the old generation and that ageing makes a transfer via pay-as-you-go pension relatively more attractive. In optimum, the implicit return on a pay-as-you-go system and the interest rate on savings should be equal to the growth rate of the economy. If people would start to save more, there would be an oversupply of capital and interest rates would decrease. A higher pay-as-you-go tax, however, would not affect its implicit return as it is always equal to the growth rate of the economy.
Keywords: E21; J11; J26; 330; Ageing; Savings; Pay-as-you-go